Pengaruh Perputaran Persediaan, Perputaran Piutang Dan Modal Intelektual Terhadap Profitabilitas Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2014 - 2016 (Penelitian Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2014 - 2016) - Nurainun Bangun; Susanto Salim; Henryanto Wijaya (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2018)
This study aims to find out how (1) the simultaneous influence inventory turnover, receivable turnover, and intellectual capital on the profitability of manufacturing companies in the period 2014-2016, (2) the partial influence of influence inventory turnover, receivable turnover, and intellectual capital variables on the profitability of manufacturing companies in the period 2014-2016. This research uses purposive sampling in taking data. The data collected will be analyzed using multiple linear analyses. The result of this research is (1) there is significant influence from inventory turnover variable to profitability, (2) there is no significant influence from receivable turnover variable to profitability, (3) there is positive significant influence from value added capital employedvariable to profitability, (4) there is positive significant influence from value added human capital variable to profitability, (5) there is positive significant influence from structural capital value added variable to profitability, (6) there is a significant effect of inventory turnover, receivable turnover,value added capital employed, value added human capital, and from structural capital value addedon profitability simultaneously.